Analysis and numerical investigation for thermal stress on arc spraying 3Cr13 coating. (1st January 2013) - Li, C.H.; Zhang, Q.; Wang, S.; Ding, Y.C.
The theoretical analysis for arc spraying 3Cr13 coating thermal stress has been made; the heat conduction temperature field and stress field model for arc spraying 3Cr13 molten drop has been built and numerical simulation has been done for theoretical model. The result is proven that: when the high temperature molten drop is deposited on the matrix, the matrix temperature is sharply rising. However the molten drop coating has a shock chilling process that the molten drop temperature is suddenly dropping from 2, 270 K to 400 K after melting to cover the matrix and finally the coating and matrix jointly drop to the room temperature 300K after 190s. The coating is exposed to tensile stress while the matrix is exposed to pressure stress. Furthermore, the lower the coating temperature and the less the matrix temperature, the smaller the radial stress that the coating and matrix are exposed to. The coating tensile stress is the minimum when the coating temperature is 1, 000 K. The flying speed of particle along with the axle appears inflection point when the spraying distance is 200 mm. When the spraying distance is less than 200 mm, the particle's flying speed accelerates with the increase of spraying distance; when the spraying distance is more than 200 mm, the flying speed decreases with the increase of spraying distance. The stimulation analysis is consistent with technological test result.